Climate change impacts on freshwater fishes: a Patagonian perspective - Becker, Leandro Anibal (2017)
The fish fauna of Patagonian lakes comprises a small, unique group of native species and several exotic ones. The consequences of environmental changes for Patagonian fish populations vary according to the physiology of the species considered. Several previously predicted facts such as extirpations, extinctions, and translocations have occurred and human actions such as transport, introduction, and stocking of exotic species suggest a more complex future. We discuss the historical biogeography of Patagonian freshwater ichthyofauna to help us better understand their present adaptations and physiological ecology. We also address potential interactions between climate change and processes such as migration, species introductions, and invasions. There is still much to learn from Patagonian fishes to comprehend how these species will endure environmental changes.